2012
DOI: 10.1080/03601234.2012.706548
|View full text |Cite
|
Sign up to set email alerts
|

Fate and distribution of fipronil on companion animals and in their indoor residences following spot-on flea treatments

Abstract: Use of fipronil {5-amino-1-[2,6-dichloro-4-(trifluoromethyl)phenyl]-4-trifluoromethyl)sulfinyl]-1H-pyrazole-3-carbonitrile CAS 120068-37-3} topical pet products on dogs and cats introduces low level residues into residences. Distribution and fate studies of fipronil on pets and in residences were performed to evaluate potential determinants of human exposure. Fipronil, desulfinyl fipronil, fipronil sulfone and fipronil sulfide were measured on hair clippings and brushed hair. The derivatives usually represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Furthermore, many flea and tick topical products contain approximately 10% fipronil and are applied directly to the skin and fur of dogs and cats, leading to human exposure through direct contact with pets. Dyk et al (2012) used a fluorescent indicator to show that these fipronil residues are easily transferred from pets to humans by way of direct contact for one week following application (Dyk et al, 2012). According to estimates from the American Humane Association, up to 46% and 39% of US households keep dogs and cats, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many flea and tick topical products contain approximately 10% fipronil and are applied directly to the skin and fur of dogs and cats, leading to human exposure through direct contact with pets. Dyk et al (2012) used a fluorescent indicator to show that these fipronil residues are easily transferred from pets to humans by way of direct contact for one week following application (Dyk et al, 2012). According to estimates from the American Humane Association, up to 46% and 39% of US households keep dogs and cats, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because human samples can be difficult to obtain and analyze due to high concentrations of endogenous chemicals and significant matrix effects which make the identification of metabolites difficult. Literature on the potential routes of human exposure includes one article by Dyk et al that describes the potential for non-occupational human exposure through contact with pets that have received fipronil applications in the form of flea and tick treatments (Dyk et al, 2012), and a few other studies that have observed fipronil in various environmental media relevant to human exposure (indoor/outdoor dust Mahler et al, 2009, wastewater Stone et al, 2014, surface water Ryberg et al, 2010; Stone et al, 2014 and residential runoff Gan et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Hair clippings of brushing of dogs treated with fipronil spot-on had <10% of the fipronil applied to the animal [ 441 ]. Low levels were found on human gloves after petting the animals.…”
Section: Toxicology Of Ectoparasiticidesmentioning
confidence: 99%
“…Environmental conditions dictate the metabolic pathway of the parent compound to form fipronil sulfone (“sulfone”) through oxidative processes, fipronil desulfinyl (“desulfinyl”) through photolytic transformation, fipronil amide (“amide”) through hydrolytic process, fipronil sulfide (“sulfide”) through anaerobic reduction, or fipronil desulfinyl amide either aerobically in soils or by hydrolysis under basic conditions (Gunasekara et al, 2007; Dyk et al, 2012). All degradates are generally more persistent than fipronil in stream sediments, with half‐lives ranging from 195 to 598 d (Lin et al, 2009).…”
mentioning
confidence: 99%